Answer:
17.60
Step-by-step explanation:
Please see the attachment for the step by step answer
The simplified form of the equation is
.
<h2>
Given that</h2>
Equation; ![\rm -9.2(8x - 4) + 0.7(2 + 6.3x)](https://tex.z-dn.net/?f=%5Crm%20-9.2%288x%20-%204%29%20%2B%200.7%282%20%2B%206.3x%29)
<h3>
We have to determine</h3>
The simplified form of the equation;
<h3>According to the question</h3>
To determine the simplified form of the equation following all the steps given below.
Equation; ![\rm -9.2(8x - 4) + 0.7(2 + 6.3x)](https://tex.z-dn.net/?f=%5Crm%20-9.2%288x%20-%204%29%20%2B%200.7%282%20%2B%206.3x%29)
<h3>
To simplify the equation multiple the terms and solve.</h3>
Then,
The simplified form of the equation is,
![\rm =-9.2(8x - 4) + 0.7(2 + 6.3x)\\ \\ = (-9.2) (8x)- (-9.2)(4) + (0.7)(2) + (0.7) (6.3x)\\ \\ =-73.6x -(-36.8) +(1.4)+(4.41x)\\ \\ = -73.6x+36.8+1.4+4.41x\\ \\ =-69.19x+38.2](https://tex.z-dn.net/?f=%5Crm%20%3D-9.2%288x%20-%204%29%20%2B%200.7%282%20%2B%206.3x%29%5C%5C%0A%5C%5C%0A%3D%20%28-9.2%29%20%288x%29-%20%28-9.2%29%284%29%20%2B%20%280.7%29%282%29%20%2B%20%280.7%29%20%286.3x%29%5C%5C%0A%5C%5C%0A%3D-73.6x%20-%28-36.8%29%20%2B%281.4%29%2B%284.41x%29%5C%5C%0A%5C%5C%0A%3D%20-73.6x%2B36.8%2B1.4%2B4.41x%5C%5C%0A%5C%5C%0A%3D-69.19x%2B38.2)
Hence, The simplified form of the equation is
.
To know more about Equation click the link given below.
brainly.com/question/26252222
Answer:
Step-by-step explanation:
4/7 x + 70 cm^3 = 3/4 x Subtract 4/7 x from both sides
3/4 x - 4/7 x = 70 cm^3 The lowest common denominator is 28
![\frac{3*7*x}{4*7} - \frac{4*4x}{4*7} = 70 cc\\\frac{21*x}{28} - \frac{16*x}{28} = 70 cc\\\frac{5x}{28}= 70cc\\](https://tex.z-dn.net/?f=%5Cfrac%7B3%2A7%2Ax%7D%7B4%2A7%7D%20-%20%5Cfrac%7B4%2A4x%7D%7B4%2A7%7D%20%3D%2070%20cc%5C%5C%5Cfrac%7B21%2Ax%7D%7B28%7D%20-%20%5Cfrac%7B16%2Ax%7D%7B28%7D%20%3D%2070%20cc%5C%5C%5Cfrac%7B5x%7D%7B28%7D%3D%2070cc%5C%5C)
5x = 70*28
5x = 1960 Divide by 5
x = 1960/5
x = 392 cc
Answer:
The functions are inverses; f(g(x)) = x ⇒ answer D
⇒ answer D
Step-by-step explanation:
* <em>Lets explain how to find the inverse of a function</em>
- Let f(x) = y
- Exchange x and y
- Solve to find the new y
- The new y = ![f^{-1}(x)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29)
* <em>Lets use these steps to solve the problems</em>
∵ ![f(x)=\sqrt{x-3}](https://tex.z-dn.net/?f=f%28x%29%3D%5Csqrt%7Bx-3%7D)
∵ f(x) = y
∴ ![y=\sqrt{x-3}](https://tex.z-dn.net/?f=y%3D%5Csqrt%7Bx-3%7D)
- Exchange x and y
∴ ![x=\sqrt{y-3}](https://tex.z-dn.net/?f=x%3D%5Csqrt%7By-3%7D)
- Square the two sides
∴ x² = y - 3
- Add 3 to both sides
∴ x² + 3 = y
- Change y by ![f^{-1}(x)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29)
∴ ![f^{-1}(x)=x^{2}+3](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3Dx%5E%7B2%7D%2B3)
∵ g(x) = x² + 3
∴ ![f^{-1}(x)=g(x)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3Dg%28x%29)
∴ <u><em>The functions are inverses to each other</em></u>
* <em>Now lets find f(g(x))</em>
- To find f(g(x)) substitute x in f(x) by g(x)
∵ ![f(x)=\sqrt{x-3}](https://tex.z-dn.net/?f=f%28x%29%3D%5Csqrt%7Bx-3%7D)
∵ g(x) = x² + 3
∴ ![f(g(x))=\sqrt{(x^{2}+3)-3}=\sqrt{x^{2}+3-3}=\sqrt{x^{2}}=x](https://tex.z-dn.net/?f=f%28g%28x%29%29%3D%5Csqrt%7B%28x%5E%7B2%7D%2B3%29-3%7D%3D%5Csqrt%7Bx%5E%7B2%7D%2B3-3%7D%3D%5Csqrt%7Bx%5E%7B2%7D%7D%3Dx)
∴ <u><em>f(g(x)) = x</em></u>
∴ The functions are inverses; f(g(x)) = x
* <em>Lets find the inverse of h(x)</em>
∵ h(x) = 3x² - 1 where x ≥ 0
- Let h(x) = y
∴ y = 3x² - 1
- Exchange x and y
∴ x = 3y² - 1
- Add 1 to both sides
∴ x + 1 = 3y²
- Divide both sides by 3
∴ ![\frac{x + 1}{3}=y^{2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%20%2B%201%7D%7B3%7D%3Dy%5E%7B2%7D)
- Take √ for both sides
∴ ± ![\sqrt{\frac{x+1}{3}}=y](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7Bx%2B1%7D%7B3%7D%7D%3Dy)
∵ x ≥ 0
∴ We will chose the positive value of the square root
∴ ![\sqrt{\frac{x+1}{3}}=y](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7Bx%2B1%7D%7B3%7D%7D%3Dy)
- replace y by ![h^{-1}(x)](https://tex.z-dn.net/?f=h%5E%7B-1%7D%28x%29)
∴ ![h^{-1}(x)=\sqrt{\frac{x+1}{3}}](https://tex.z-dn.net/?f=h%5E%7B-1%7D%28x%29%3D%5Csqrt%7B%5Cfrac%7Bx%2B1%7D%7B3%7D%7D)